2011
DOI: 10.1016/j.seizure.2011.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association of ABCB1 haplotypes on five loci with response to treatment in epilepsy

Abstract: Approximately one third of newly treated epilepsy patients do not respond to antiepileptic drugs (AEDs). Overexpression of P-glycoprotein (P-gp) efflux transporter has been proposed to have a critical role in causing resistance to AEDs. P-gp is a product of the ATP-binding cassette subfamily B member 1 (ABCB1) gene. The purpose of this study was to investigate a possible link between ABCB1 rs3789243 C>T, C1236T, G2677T/A, rs6949448 C>T, and C3435T haplotypes with response to carbamazepine (CBZ) or sodium valpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 28 publications
2
13
0
1
Order By: Relevance
“…The c.3435C>T variant has attracted most attention as a critical variant correlated with altered expression levels of P-gp [34]. In this study, ABCB1 3435CC carriers had higher CDR CBZ than 3435CT carriers, while a previous study on the Chinese population found a difference between homozygous mutant (3435TT) and wild-type (3435CC) [9].…”
Section: Discussionmentioning
confidence: 55%
“…The c.3435C>T variant has attracted most attention as a critical variant correlated with altered expression levels of P-gp [34]. In this study, ABCB1 3435CC carriers had higher CDR CBZ than 3435CT carriers, while a previous study on the Chinese population found a difference between homozygous mutant (3435TT) and wild-type (3435CC) [9].…”
Section: Discussionmentioning
confidence: 55%
“…The AEDs used in each selected study and their status as substrates of P-gp are presented in Table 2; the status of AEDs as substrates of P-gp were identified according to the description of three review articles (Zhang et al, 2012;Stępień et al, 2012;Potschka and Luna-Munguia, 2014). Genotype distributions in the drug-responsive patient groups of all studies were checked for HWE, and four studies were excluded because of their deviation from HWE (Lakhan et al, 2009;Sánchez et al, 2010;Haerian et al, 2011b;Subenthiran et al, 2013; Table 3). …”
Section: Study Characteristicsmentioning
confidence: 99%
“…Some studies were unable to prove an association between G2677T/A polymorphism and resistance to AEDs (Kim et al, 2006;Shahwan et al, 2007;Vahab et al, 2009;von Stülpnagel et al, 2009;Grover et al, 2010;Dong et al, 2011;Meng et al, 2011;Sayyah et al, 2011;Haerian et al, 2011b;Seven et al, 2014), while others reported a significant association (Hung et al, 2007;Kwan et al, 2009;Subenthiran et al, 2013); moreover, a study from India indicated an association of allele A with drug-resistant epilepsy (Kumari et al, 2011). In addition, a recent meta-analysis involving G2677T/A polymorphism (Haerian et al, 2011a) did not find a significant association between G2677T/A polymorphism and resistance to AEDs in epilepsy (P = 0.07-0.96).…”
Section: Studymentioning
confidence: 99%
“…Haplotype is the combination of single nucleotide polypeptides that are located and interconnected in a specific region of chromosome and that tend to pass down to the descendants via overall heredity. Most chromosomal regions have only a few common haplotypes (each with ≥5% frequency), which represent the majority of polymorphism between men and women in a group (22). The identification of haplotype is usually dependent on a group of SNP, i.e., a group of SNPs in a specific region of chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of haplotype is usually dependent on a group of SNP, i.e., a group of SNPs in a specific region of chromosome. At present, haplotype data are obtained by statistical calculation, which is based on the distribution frequency of the genotypes in the population (22). In the present study, SHEsis software was used based on the maximum likelihood algorithm to produce the haploid inference.…”
Section: Discussionmentioning
confidence: 99%